The intention to share a sustainability communication about a tourism destination - Maria Del Mar Garcia de los Salmones; Angel Herrero; Patricia Martínez García de Leaniz (Spanish Journal of Marketing-ESIC)
Purpose – This paper aims to analyse the determinants of the intention to share a post about an environmental issue posted by a tourism destination on Facebook. The authors use the stimulus-organism-response (SOR) model as a theoretical framework and consider cognitive variables (destination social responsibility, tourist social responsibility and three types of congruence) as antecedents of emotions and of the tourists’ response (intention to share). Specific factors related to the social platform (attachment and active use of social media) are also included. Design/methodology/approach – The model was tested for two destinations with different positioning (green tourism versus sun and beach). For the sampling strategy, the authors conducted an online poll targeting Facebook users who had undertaken at least one trip in the previous year. The sample consisted of 1,001 individuals. Findings – The empirical evidence obtained indicates that consumer–cause congruence is the most important variable for explaining the intention to share the post for both destinations, with the destination–cause congruence being non-significant. The authors also observed that active participation on the social network stimulated the intention to share this specific content. Originality/value – Unlike prior research, this paper examined consumer motivators for engaging with online corporate social responsibility content for tourism destinations, specifically focusing on destination social responsibility in sustainable tourism. The model also incorporates three types of congruence, revealing variations in their impact on explaining the intention to share sustainability-related posts. La Intención de Compartir Comunicación Sobre Sostenibilidad de Un Destino Turístico Objetivo – Este trabajo analiza los determinantes de la intención de compartir una publicación sobre un tema ambiental publicada por un destino turístico en Facebook. Utilizamos el modelo estímulo-organismo-respuesta (SOR, por sus siglas en inglés) como marco teórico y consideramos variables cognitivas (responsabilidad social del destino, responsabilidad social del turista y tres tipos de congruencia) como antecedentes de las emociones y de la respuesta de los turistas (intención de compartir). También se incluyen factores específicos relacionados con la plataforma social (apego y uso activo de las redes sociales). Diseño/metodología/enfoque – El modelo se probó para dos destinos con diferentes posicionamientos (turismo verde versus sol y playa). Para la estrategia de muestreo, realizamos una encuesta en línea dirigida a usuarios de Facebook que habían realizado al menos un viaje en el año anterior. La muestra consistió en 1.001 individuos. Resultados – La evidencia empírica obtenida indica que la congruencia consumidor-causa es la variable más importante para explicar la intención de compartir la publicación en ambos destinos, mientras que la congruencia destino-causa no fue significativa. También observamos que la participación activa en la red social estimuló la intención de compartir este contenido específico. Originalidad – A diferencia de investigaciones previas, este artículo examinó los motivadores del consumidor para interactuar con contenido de responsabilidad social corporativa en línea de destinos turísticos, enfocándose específicamente en la responsabilidad social del destino en el turismo sostenible. El modelo también incorpora tres tipos de congruencia, revelando variaciones en su impacto en la explicación de la intención de compartir publicaciones relacionadas con la sostenibilidad. 分享旅游目的地可持续性传播信息的意图 研究目的 – 本研究分析了在Facebook上分享旅游目的地发布的环保问题帖子的意图决定因素。我们使用刺激-有机体-反应（SOR）模型作为理论框架, 并考虑了认知变量（目的地社会责任、游客社会责任和三种类型的一致性）作为情绪和游客反应（分享意图）的前因。此外, 还包括与社交平台相关的特定因素（社交媒体的依赖度和活跃使用）。 设计/方法论/研究方法 – 该模型针对两个具有不同定位（绿色旅游与阳光沙滩）的目的地进行了测试。我们通过在线问卷调查了过去一年内至少进行过一次旅行的Facebook用户, 最终样本量为1,001人。 研究发现 – 研究结果表明, 对于两个目的地, 消费者与环保事业一致性是解释分享帖子的意图的最重要变量, 而目的地与环保事业的一致性并不显著。我们还发现, 社交网络的活跃参与能激发用户分享此类特定内容的意图。 原创性 – 与以往研究不同, 本文探讨了消费者参与在线企业社会责任内容的动机, 特别关注于可持续旅游中的目的地社会责任。该模型还引入了三种类型的一致性, 并揭示了它们在解释分享可持续性相关帖子意图中的影响差异。